The Effect of Beethoven's Classical Music Therapy on the Ability to Control Auditory Hallucinations in the Dewa Ruci Room of Dr. Amino Gondohutomo Mental Hospital, Central Java - Julian Debora Talasi; Dwi Indah Iswanti (BIOSAINSTEK, 2026)
Auditory hallucinations are capturing sounds or complete dialogues from two or more individuals in which the patient is instructed to perform actions that are sometimes risky (Madepan et al., 2021). Nursing care using the method of reprimanding techniques, conversations, doing activities and taking medication as well as providing Beethoven's Classical Music Therapy to patients with Auditory Hallucinations to see the patient's ability to control the hallucinations experienced by the patient. Non-pharmacologic approaches such as Beethoven's classical music therapy are considered useful in helping respondents manage hallucinations independentlyDescribe the method of reprimanding techniques, conversations and Beethoven's classical music therapy on the ability to control auditory hallucinations. This case study involved three patients (Mrs. K, Mrs. H, Mrs. D) who show ed symptoms of auditory hallucinations. And the Implementation of Freezing carried out by the researcher was for 4 days, in patients Mrs. K (02-06-2025), Mrs. H (06-07-2025), and Mrs. D (06-12-2025) through a gradual approach, namely providing hallucination rebuke techniques, training patients to converse, taking medication, and providing Beethoven classical music therapy, inputting the techniques taught into the patient's daily schedule. Data analysis used was frequency and percentage distribution. There was a significant decrease in the indicators of verbalization of hearing whispering voices and hallucinatory behavior. The scores of the three respondents decreased from the "increased" category on the first day to "decreased" on the fourth day, which showed the effectiveness of Beethoven classical music therapy intervention. rebuke, conversation, and Beethoven classical music therapy proved effective in controlling auditory hallucinations.